Amplitudes of muscle activity during early practice trials compared with those of a well-learned skill - Heise, G. D.; Christiansen, C. (Annual Meeting of the American Society of Biomechanics. (Presented on poster September 9-10, 2004 at the ASB meeting in Portland), 2004)
Traditional skill acquisition research has focused on the outcome or goal of a movement as the primary dependent variable. Conclusions from these studies have implications for skill training concerns (e.g., training schedules, types of feedback), however, little is added to our understanding of how the learner acquires control for a certain skill. From a dynamical systems perspective, a learner will acquire the most economical coordination strategy available, which may include exploiting reactive forces present in the link-segment system (Bernstein, 1967). Within this context, Vereijken et al. (1992) studied a multijoint task and found significant improvements in task outcomes and movement dynamics by the 20th practice trial. Changes in muscle activation during early stages of practice, however, are not as well known (Young & Marteniuk, 1995). Therefore, the purpose of this study was to examine the changes in muscle activity during the first day of practice of a multijoint, "ski-simulation" task. Specifically, we examined the ratios of EMG amplitudes between knee extension and flexion. In conclusion, extension-flexion EMG amplitudes early in practice did not reach levels shown by subjects late in practice.